Extending Green Supply Chain Management to the Mining Sector in South Africa: Implications for Corporate Performance - Ngcobo, Abednigo Mkhetheni; Mafini, Chengedzai; Loury Okoumba, Welby (African Journal of Inter/Multidisciplinary Studies, 2022)
The South African mining sector faces numerous challenges that limit the performance of firms, chief among them environmental management, labour, and operational issues. An important research gap exists on how the adoption of green supply chain management (GSCM) can contribute to the mitigation of some of these challenges. This study investigates the connection between GSCM, employee satisfaction, operational and relational efficiency, and enterprise performance in the mining sector in South Africa. The study employed a quantitative method using a cross-sectional survey design. A structured research questionnaire was used to collect data from supply chain professionals at two leading mining firms based in the North-West Province, South Africa. The collected data were analysed using a structural equation modelling procedure based on the partial least squares technique. The study reveals the positive influence of GSCM on employee job satisfaction, operational efficiency, relational efficiency, and enterprise performance. The study also confirms that relational efficiency and operational efficiency both exert a positive influence on enterprise performance. However, employee job satisfaction exerted no influence on enterprise performance. GSCM itself exerted a direct positive influence on enterprise performance. The application of GSCM in the mining sector should be recognised as part of the solutions to motivating supply chain professionals and stimulating important internal and external efficiencies, leading to the enhanced performance of the firm.